ANALISIS TIPE BATUAN DASAR PEMBENTUK NIKEL LATERIT PADA BLOCK X KABUPATEN BANGGAI, PROVINSI SULAWESI TENGAH - Novariani Payuyu; Aang Panji Permana; Ronal Hutagalung (Jurnal Sains Informasi Geografi (J SIG), 2022)
Nickel is an important strategic resource and has become a key material for the development of modern aerospace and defense industries, infrastructure and technology. The research area is located in block X, Banggai Regency, Central Sulawesi. The purpose of this study is to analyze the type of bedrock using petrographic analysis based on the research location. The research method used is direct observation in the field and laboratory analysis. The morphology of the research site belongs to the geomorphological unit of denudational origin, divided into two topography, namely denudational hills with gentle slopes (4-8° or 7-15%) and denudational hills with moderate-sloping slopes (8-16° or 15-30%). The bedrock that has been successfully analyzed at the research site is a cretaceous serpentinized peridotite unit.